Thermogravimetric and Kinetic Analysis of Different Agro-Industrial Wastes Under Nitrogen Atmosphere - Echegaray, Marcelo Eduardo (2015)
In this work, the behavior during thermal treatment processes of marcs, stalk and peach pits, from the wineries, canning and the jam industries was studied.The immediate and elemental analysis are realized.The studied agro-industrial wastes have higher water content than 30%, suggesting that these wastes should be dried before the thermal treatment. The ash contents are smaller than 7%, considering these contents low.The ultimate analysis showed higher oxygen concentrations present in the studied agroindustrial wastes, decreasing the HHV. The trace elements contents in these wastes are determined too. These elements remain in the char/ash fraction of the different pyrolysis products, during thermal treatment under inert atmosphere. Thermal decomposition of the studied wastes was studied in inert nitrogen atmosphere. Their decompositions proceed through three stages of weight loss, dehydration, active pyrolysis and passive pyrolysis. The maximum weight loss took place during the active pyrolysis step. In this stage, the peach pits exhibit the most prominent due to the higher content of hemicellulose. Another reason can be the difference of elements concentrations such us the Ca. This element is present in smaller concentration in the peach pits.Themarcs decomposing at lower temperature compared with the other biomasses. It also has the lowest mass loss. This behavior might be associated with the highest content of extractives in its structure. The higher value of activation energy was obtained for the peach pits, meaning slower reaction. The reaction orders were smaller than 1 for the studied agro-industrial wastes.